Extended Kalman Filter for Sensorless Fault Tolerant Control of PMSM with Stator Resistance Estimation - Mongi Moujahed; Bilel Touaiti; Hechmi Benazza; Mohamed Jemli; Mohamed Boussak (Institute of Advanced Engineering and Science, 2018)
This paper aims to provide a high performance sensorless control based on an Extended Kalman Filter (EKF) applied to fault-tolerant PMSM drive system with stator-resistance estimation. It proposes a fast method of fault switches detection in the power converters. The considered drive is composed of three phases PMSM and a four leg three phase’s inverter when the fourth is the redundant leg. After a short-switch fault occurrence, the redundant leg replaces the faulty leg. The simulation results verify that the proposed control method and the fault tolerant inverter ensure the high reliability and continuously operation of the sensorless vector control PMSM system under inverter fault.